2019
DOI: 10.1515/commun-2018-2005
|View full text |Cite
|
Sign up to set email alerts
|

Personalization 2.0? – Testing the personalization hypothesis in citizens’, journalists’, and politicians’ campaign Twitter communication

Abstract: This paper advances the research on personalization of political communication by investigating whether this process of focusing on politicians instead of political issues plays a role on Twitter. Results of a content analysis of 5,530 tweets posted in the run-up to the German federal election provide evidence that Twitter communication refers more often to politicians than to issues. However, tweets containing personal characteristics about political leaders play only a marginal role. When distinguishing amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Media personalization has mainly been studied in the context of newspapers, and personalization on social media has attracted little scholarly attention (Otto et al, 2018;Rahat & Kenig, 2018). The argument that growing use of social media would increase the personalization of politics seems to be based more on scholars' perception of social media as an inherently personal media than on empirical evidence (Rahat & Kenig, 2018).…”
Section: U M C Smentioning
confidence: 99%
See 1 more Smart Citation
“…Media personalization has mainly been studied in the context of newspapers, and personalization on social media has attracted little scholarly attention (Otto et al, 2018;Rahat & Kenig, 2018). The argument that growing use of social media would increase the personalization of politics seems to be based more on scholars' perception of social media as an inherently personal media than on empirical evidence (Rahat & Kenig, 2018).…”
Section: U M C Smentioning
confidence: 99%
“…Personalization of politics in social media has steadily attracted research in the context of election campaigns, where personalized elements have been identified in social media campaign posts in single-country studies (e.g. Kruikemeier et al, 2014;Larsson, 2019;Meeks, 2017;Otto et al, 2018;Small, 2017;Grusell & Nord, 2020;Kannasto, 2021;Kannasto et al, 2023). Perhaps the most comprehensive analysis so far has been conducted by Rahat and Kenig (2018), who analyzed personalization in the Facebook and Twitter accounts of politicians from 25 countries.…”
Section: U M C Smentioning
confidence: 99%
“…Previous research and literature reviews have shown that media reporting of politics has become more personalized over time (Karvonen, 2009;Adam and Maier, 2010). However, this applies only to traditional media, as the personalization of political communication in the context of social media has not been systematically studied so far (Rahat and Kenig, 2018), although individual studies have shown that politicians' social media posts also contain personalized elements (e.g., Kruikemeier et al, 2013;Small, 2017;Bronstein et al, 2018;Rahat and Kenig, 2018;Otto et al, 2018). There is a lack of research analyzing personalization in the context of hybrid media systems.…”
Section: Research Questionsmentioning
confidence: 99%
“…Nevertheless, exactly how this happens and for what purposes have so far gained little scholarly attention. Equally little is known about how the personalization trend has been influenced by the emergence of the hybrid media system, as personalization is still mostly analyzed in the separate contexts of traditional media or (to a lesser extent) social media (Otto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%